URGENSI CIVIC EDUCATION DALAM KEHIDUPAN BERNEGARA - Asrori Mukhtarom; Desri Arwen; Ety Kurniyati (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2019)
Civic education in each country has their respective goals in accordance with the value system and political system adopted by a country. Objectives play a very important role, because they will direct all teaching activities and color the other components. To be clear and focused, the purpose of civic education must be based on the values in the philosophy of a country, and accommodate the development of the demands and needs of society. In Indonesia, civic education aims to form good citizens who have citizenship knowledge about their rights and obligations as a citizen, citizenship skills capable of participating in state affairs, and have citizenship attitudes / values in accordance with the ideology of Pancasila. Civic education is formally provided at every level of education through subjects and courses in Civic Education. This research is a qualitative study that is a literature study (library research) that uses books and other literature as the main object. Keywords : Objectives, Civic Education, Indonesia